2006
DOI: 10.1177/07419325060270030601
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Task Engagement Using Preference or Choice-Making

Abstract: Frequent reprimands, low expectations, and infrequent praise characterize the daily school experiences of many students who display problem behaviors. This review evaluates preference and choice-making as possible interventions for improving these school experiences. Findings from 15 studies suggest that preference and choice-making may improve both academic performance and behavior. However, an underlying behavioral mechanism may more parsimoniously account for the effects attributed to each intervention. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 51 publications
(206 reference statements)
0
13
0
Order By: Relevance
“…Although our participants paid more attention, generated creative ideas, and put more emotional investment in student-selected tasks, they simultaneously seemed to encounter difficulties with conditions in which they were given freedom and had to make choices, which is consistent with Appel and Gilabert (2002). It is undeniable that offering choice-making opportunities may be the key to enabling students to feel interested in tasks, maximizing their task engagement, and developing creativity (Flowerday & Schraw, 2000;Morgan, 2006). However, it should be noted that more freedom or increased choices may be unappealing or, sometimes, daunting, because it forces individuals to gather more information than they currently possess to make good decisions (Schwartz, 2000).…”
Section: Effect Of Task Design On Student Engagementmentioning
confidence: 55%
“…Although our participants paid more attention, generated creative ideas, and put more emotional investment in student-selected tasks, they simultaneously seemed to encounter difficulties with conditions in which they were given freedom and had to make choices, which is consistent with Appel and Gilabert (2002). It is undeniable that offering choice-making opportunities may be the key to enabling students to feel interested in tasks, maximizing their task engagement, and developing creativity (Flowerday & Schraw, 2000;Morgan, 2006). However, it should be noted that more freedom or increased choices may be unappealing or, sometimes, daunting, because it forces individuals to gather more information than they currently possess to make good decisions (Schwartz, 2000).…”
Section: Effect Of Task Design On Student Engagementmentioning
confidence: 55%
“…This finding is similar to that found by Reinhartsen, Garfinkle, and Wolery (2002), who in their study of 2-year-olds with autism, found that when the child initiated his or her own play, the play lasted for a longer duration of time, in comparison to scenarios when the child was given two choices or presented with one activity. In a meta-analysis of 15 studies, Morgan (2006) concluded that when students are able to make their own choices, problem behaviors decrease, increasing their productivity and appropriate behaviors. In a study of reinforcement preferences, Fenerty and Tiger (2010) also found choice to be preferred in comparison to a no-choice condition.…”
Section: Discussionmentioning
confidence: 99%
“…Choice making and preference are simple interventions that have shown positive effects in reducing problem behavior and increasing task engagement (Morgan, 2006). Choice making allows students to indicate choice in the activities, sequence of activities, or rewards.…”
Section: Desirable Tasksmentioning
confidence: 99%
“…Cosden, Gannon, and Haring (1995) found greater effects for a combination of the choice of the task and the reward compared to the choice of the task or reward alone. Preference, on the other hand, promotes engagement in activities that are more reinforcing or liked by the child (Morgan, 2006). Research has found no differences in the effects of teacher or student selected tasks (Cole, Davenport, Bambara, & Ager, 1997).…”
Section: Desirable Tasksmentioning
confidence: 99%
See 1 more Smart Citation